Mitral Valve Surgery via Partial Upper Sternotomy: Closing the Gap between Conventional Sternotomy and Right Lateral Minithoracotomy - Oezpeker, Cenk; Barbieri, Fabian; Hoefer, Daniel; Schneider, Bastian; Bonaros, Nikolaos; Grimm, Michael; Mueller, Ludwig (The Thoracic and Cardiovascular Surgeon, 2019)
Background Minithoracotomy (MT) has gained broad acceptance for mitral valve surgery (MVS) in the last decade. In the presence of defined limitations of MT, however, full sternotomy (FS) is still widely preferred. We assume that the less investigated partial upper sternotomy (PS) will permit the gap between MT and FS in MVS to be closed. The purpose of this study is to investigate a valid less invasive alternative to MT for isolated MVS or multivalve surgery.Methods This retrospective analysis includes data on 1,639 patients, who underwent either isolated or combined primary MVS at our department from May 2011 to August 2017. Out of these, 663 patients were operated via MT access. One-hundred three patients had been judged as not suitable for MT but feasible for PS approach in which 53.4% (n = 55) had isolated MVS and 46.6% patients (n = 48) underwent multivalve surgery. Concomitant myocardial revascularization was performed in 2.9% of the study patients (n = 3).Results Operative, 90-day, and 1-year mortality in the PS-cohort was 0, 1.0% (n = 1), and 3.3% (n = 3), respectively. During a median follow-up time of 1,115 days (interquartile range 398–1806), all-cause mortality was 5.8% (n = 6). Operative times for cardiopulmonary-bypass and cross-clamping were 167 minutes (140–198) and 107 minutes (93–132), respectively. Median length of stay at the intensive care unit and hospital was 1 (1–2) and 7 days (7–10), respectively.Conclusion The presented results demonstrate that there is a cohort of patients, who are not candidates for MT in MVS but may be operated successfully by an alternative less invasive approach.
Keywords: mitral valve surgery; partial upper sternotomy; multivalve surgery; minimally invasive